Le tourisme dans la Caraïbe, un moteur du développement territorial - Michel Desse; Jusline Rodne Jeanty; Monique Gherardi; Simon Charrier (IdeAs)
The Caribbean islands constitute a dynamic and old touristic area, but it depends on the international economic context. Different forms of tourism meet the requirements of varied customers and are more or less appropriated by insular actors, allowing local development. The level of development generally leads to a strong appropriation by the populations and a multiplication of activities and actors that work in connection with the touristic sector.